2015
DOI: 10.1111/jir.12226
|View full text |Cite
|
Sign up to set email alerts
|

The emergence and stability of attention deficit hyperactivity disorder in boys with fragile X syndrome

Abstract: Background Children with fragile X syndrome (FXS) are at high risk for developing a range of behavioral disorders, including Attention Deficit/Hyperactivity Disorder (ADHD) and autism spectrum disorders (ASD). However, very few studies have investigated the comorbid profile of FXS and ADHD and the possible dissociation from the FXS and ASD profile. The present study examined the relationship of childhood temperament characteristics of the Surgency facet (activity level, impulsivity, approach, shyness, and smil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 67 publications
2
22
1
2
Order By: Relevance
“…Grefer et al . () concluded that boys with FXS demonstrate a unique developmental phenotype with respect to the etiology of attentional difficulties, as the same pattern of results was not observed for typically developing boys in this study.…”
supporting
confidence: 76%
See 4 more Smart Citations
“…Grefer et al . () concluded that boys with FXS demonstrate a unique developmental phenotype with respect to the etiology of attentional difficulties, as the same pattern of results was not observed for typically developing boys in this study.…”
supporting
confidence: 76%
“…impulsivity) conferring risk with respect to ADHD, and others, namely, smiling and laughter, buffering the risk for maladaptive behaviour (Grefer et al . ). Additional research is needed to clarify the role of the different facets of positive emotionality with respect to emerging symptoms of developmental psychopathology for children with FXS and other neurodevelopmental conditions.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations